Dataset_EI_Age in Unemployed. - Gómez-Hombrados, Jorge; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
The main goal of this study was to examine the moderating role of age in the relationship between emotional intelligence (EI) and mental health indicators among unemployed individuals. A sample of 401 unemployed participants were evaluated in EI, depressive symptoms, happiness. Moderation analyses showed that age moderated the relationship between EI and depressive symptoms, after controlling gender and length of unemployment, showing a stronger association among younger participants with lower EI abilities. However, this pattern was not found for happiness. These findings address knowledge gaps regarding age-EI interactions within mental health contexts and age's moderating effect in unemployment stage. Also, it is highlighted the importance of developing targeted EI training interventions to mitigate the negative mental health effects of unemployment, especially among vulnerable demographic groups like young unemployed individuals.
Keywords: Inteligencia emocional; Depresión mental - Síntomas; Jóvenes - Salud mental; Desempleo - Aspectos psicológicos; Felicidad; Edad; Emotional intelligence; Age; Depressive symptoms; Happiness; Unemployment; Unemployed youth